Toward Climate-Resilient Development in Nigeria - Cervigni, Raffaello (World Bank, 2015)
If not addressed in time, climate change is expected to exacerbate Nigeria?s current vulnerability to weather swings and limit its ability to achieve and sustain the objectives of Vision 20:2020 [as defined in http://www.npc.gov.ng /home/doc.aspx?mCatID=68253].